The regional Cretaceous development of the southeastern part of the Norwegian Barents Sea- from seismic interpretation - Heiberg, Vegard (UiT Norges arktiske universitet, 2018)
This study sheds new light on the regional Cretaceous development of the southeastern part of the Norwegian Barents Sea. The study area is in the former disputed area between Norway and Russia, which after the agreement on the new borders in 2010 was opened to petroleum activity in 2013. Consequently, the southeastern Barents Sea is still a frontier area with less scientific knowledge, compared to the adjacent onshore/offshore areas of Norway and Russia. Here, seismic interpretation have provided increased geological knowledge about the paleo-environment in Early Cretaceous by the use of new 2D data acquired by the Norwegian Petroleum Directorate (NPD) in 2011/2012. Five seismic sequences (S0-S4) have been defined, and geometry and trajectories for identified seismic clinoforms has been described in order to elucidate the depositional history of the study area. This study revealed a successive displacement of the shelf break southwestwards during Early Cretaceous. Furthermore, shelf-edge clinoforms prograded from the northeast towards the southwest, with the main source of sediments located in a hinterland towards the north/northeast. This source area has been related to the uplift of the northern Barents Shelf in Early Barremian-Early Aptian times caused by magmatic activity, also referred to as the High Arctic Large Igneous Province (HALIP). Cyclic variations in the stratigraphic successions suggested fluctuating sea levels during the Early Cretaceous. Post-depositional doming and faulting events, induced by halokinetic movements have altered the Lower Cretaceous successions in the southeastern Barents Sea.